Mengenal Wadi’ah dan Hawalah Dalam Fiqih Muamalah - Muhammad Ronaydi (CV Kalimasada Group, 2023)
The research investigates one of the muamalah fiqh products that is also developing along with the sharia economy, namely the Wadi'ah and hawalah processes, where this process has begun to be practiced and is also widely used in every transaction in sharia financial institutions. Therefore, the main focus of this paper is to discuss the meaning of Wadi'ah and Hawalah. This research uses a descriptive qualitative analytical approach, with a library research method (Library Research). The result of this writing is that etymologically Wadi'ah is something that is entrusted while in terminology it is an agreement to entrust something to a certain party in order to always maintain the safety, security and integrity of what has been entrusted. The law of wadi'ah is permissible. Etymologically, hawalah is a transfer, while in terminology it is a transfer of a person's debt to another party to pay the debt accompanied by a sense of mutual trust and agreement. The law of hawalah is permissible.